The influence of the silicate slag composition on copper losses during smelting of the sulfide concentrates - Živković Živan; Mitevska N.; Mihajlović Ivan; Nikolić Đorđe (Journal of Mining and Metallurgy. Section B: Metallurgy, 2009)
This paper presents the results of multi-linear regression analysis (MLRA) of the slag composition (SiO2, FeO, Fe3O4, CaO, Al2O3) and the content of copper in the matte on resulting copper content in the slag during smelting of the sulfide concentrates in the reverberatory furnace. When comparing results obtained with MLRA model calculations with values measured at industrial level high degree of fitting is obtained (R2 = 0.974). This indicates that slag composition and content of copper in the matte influences the copper losses in the waste slag with the probability of 95 %.